1992
DOI: 10.1111/j.1365-2222.1992.tb00153.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of perennial rhinitis with Trichophyton infection

Abstract: Trichophyton was recently reported to be the cause of respiratory allergy in patients with severe bronchial asthma. We describe eight patients with perennial rhinitis in combination with skin or toe-nail infection, in whom Type I hypersensitivity reaction to Trichophyton was confirmed by skin test, RAST and nasal provocation. When treated with oral fungicidal therapy, there was significant improvement in both their skin and nasal symptoms. Local therapy produced only a mild, transient improvement. We emphasize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…That study provided the strongest evidence yet of a causal role for dermatophyte antigens in asthma. In support of this, subsequent studies described the improvement of asthma or allergic rhinitis symptoms after oral antifungal therapy (58,68,116). Dermatophyte antigens have also been implicated in the pathogenesis of urticaria based on abatement of symptoms after treatment of tinea pedis (117).…”
Section: Background: Historical Perspectivementioning
confidence: 69%
See 1 more Smart Citation
“…That study provided the strongest evidence yet of a causal role for dermatophyte antigens in asthma. In support of this, subsequent studies described the improvement of asthma or allergic rhinitis symptoms after oral antifungal therapy (58,68,116). Dermatophyte antigens have also been implicated in the pathogenesis of urticaria based on abatement of symptoms after treatment of tinea pedis (117).…”
Section: Background: Historical Perspectivementioning
confidence: 69%
“…However, more recent studies corroborate Jones' theory that exposure to fungal antigens could induce allergic inflammatory responses in the respiratory tract. Several reports have provided evidence of a role for dermatophyte sensitivity in both asthma and allergic rhinitis (42,58,68,90,92,104,115,116) (Table 1). In a placebo-controlled challenge study, Ward et al showed that eight patients with perennial asthma and chronic tinea infection developed bronchial hyperreactivity after nasal challenge with a T. tonsurans extract (115).…”
Section: Background: Historical Perspectivementioning
confidence: 99%
“…Nucleotide and deduced amino acid sequences of recombinant Tri r 4. The NH 2 -terminal amino acid residues (positions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] contain the conserved features of a signal peptide with a predicted cleavage site between Ala 19 and Phe 20 . Underlined regions represent amino acid sequences previously obtained for the NH 2 terminus and for six enzymatically generated peptides of natural Tri t 4.…”
Section: Methodsmentioning
confidence: 99%
“…rhinitis, allergic hypersensitivity diseases. [26][27][28][29] Studies have shown that podiatrists have antibodies to this organism, suggesting routine exposure to it; 21 30 31 hypersensitivity reactions to nail dust have also been proposed. [30][31][32] A number of studies 20 33-37 report that efficiency, and therefore effectiveness of LEVs vary with drill type, speed, burr shape, size, and coarseness/abrasiveness of the burr.…”
Section: Air Sampling Studiesmentioning
confidence: 99%